2003
DOI: 10.1038/sj.bjc.6601122
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase-9 expression levels and prognosis in human breast cancer: association with treatment outcome

Abstract: Here, we set out to assess CA9 expression levels by real-time quantitative RT -PCR in breast cancer tissue samples obtained from 253 patients, and correlated those with relapse-free (RFS) survival. The median follow-up time was 75 months (range 2 -168 months). CA9 expression was mainly found in high-grade, steroid receptor negative cancer tissues. CA9 levels were not significantly associated with RFS (P ¼ 0.926, hazard ratio (HR) ¼ 0.99, 95% CI ¼ 0.80 -1.22) in the total cohort of 253 patients. In multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
78
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 25 publications
6
78
3
Order By: Relevance
“…This is in keeping with our studies in the neoadjuvant context, in which CAIX was associated with a shorter relapse-free survival in patients treated with CMF (Generali et al, 2006a, b), and in patients treated in the adjuvant setting, in which CAIX measured by RT -PCR was associated with chemoresistance (Span et al, 2003). Thus, these data suggest that CAIX is predictive rather than prognostic.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This is in keeping with our studies in the neoadjuvant context, in which CAIX was associated with a shorter relapse-free survival in patients treated with CMF (Generali et al, 2006a, b), and in patients treated in the adjuvant setting, in which CAIX measured by RT -PCR was associated with chemoresistance (Span et al, 2003). Thus, these data suggest that CAIX is predictive rather than prognostic.…”
Section: Discussionsupporting
confidence: 72%
“…In this series, those patients with tumours of either a basallike phenotype or expressing CAIX were associated with an adverse outcome. Nevertheless, in this study and in others reported earlier, CAIX expression is also positively correlated with high tumour grade and size (Chia et al, 2001;Span et al, 2003), the former feature also characteristic of basal tumours. Thus, hypoxic stress may not be part of the basal intrinsic subtype but might be due to an association with grade.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…30 In addition, CA9 transcription, detected by either semiquantitative or quantitative RT-PCR, has been associated with malignant breast tissues and treatment outcome. 18,37 Therefore, CA9 was chosen as a cancer-related marker for our study. We confirmed its expression in primary vulvar carcinomas by both immunohistochemistry and nested RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24] Furthermore, only one study evaluated the response of tamoxifen according to HIF-1 expression and an independent report analyzed the predictive value of CA IX measured by RT-PCR. 21,24 However, no study addressed the impact on survival and treatment outcome of both together, HIF-1a and CA IX, in breast cancer. Because of the controversial results and also because we speculated that combination of HIF-1a and CA IX, one of its downstream target, might provide additional information, we performed the present study.…”
mentioning
confidence: 99%